Stromal Tumor Infiltrating Lymphocytes (sTILs) Were Associated with a Higher Grade and a Lower Stage of Indonesian Triple Negative Breast Cancers - Widodo, Irianiwati (Asian Pacific Organization for Cancer Prevention, 2022)
Objective: This study aimed to investigate the association of sTILs with clinicopathological parameters and overall survival (OS) in patients with triple negative breast cancer (TNBC). Methods: One hundred and twenty-five paraffin embedded tissue of patients with TNBC, collected from Dr. Sardjito General Hospital Yogyakarta, Indonesia, between 2008-2017, were used in this study. Stromal TILs were examined from hematoxylin and eosin (H&E)-stained samples, and classified as either low or high score using 20 cut-off. Analysis of the association of sTILs with clinicopathological parameters, relative risk (RR) and OS used 95 confidence interval (CI) with significance set as p<0.05. Results: The higher proportion of TNBC patients in this study were ≥40 years old (83.3), high tumor grade (68), tumor stage >IIIa (56), alive (50.4), and with low sTILs (54.4). The results showed significant association between sTILs and a higher grade or a lower stage of tumor (B = 0.259, 95CI = 0.090-0.468, p = 0.004 and B = -0.255, 95CI = -0.433 - -0.080, p = 0.005, respectively ). Meanwhile sTILs were not associated with age at diagnosis (B = 0.027, 95CI = -0.193 – 0.264 p = 0.758 nor 3-year OS of patients (HR = 0.342, 95CI = 0.41 - 1.43 p = 0.402). Conclusion: The results indicate that sTILs may serve as an additional pathological parameter for TNBC. © This work is licensed under a Creative Commons Attribution-Non Commercial 4.0 International License